Mitigating Youth’s Problems through Vedic Approach with Reference to Pedagogical Quest - Poudel, Sharada Dhakal; Jnawali, Damodar (Perspectives on Higher Education, 2024)
This research paper aims to examine the problems of youth people in Nepalese societies. Most of the youth people are suffering from various types of problems like addiction, stress, anxiety, and depression. The main theme of this study is to find out the Vedic ways to make problem free youths of today. I applied relational narrative & ethnographic qualitative research design because this research is underpinning the human behavior and attributes. Data was collected through using different tools like observation, interviews, focus group discussion, preparing case studies and document analysis. Data analysis and interpretation was based on field narratives, research documents and Vedic scholar’s inputs. The findings of this study were interpreted to relate with psychological, socio cultural, intergenerational and youth representative theories. I drew the Nature Based Education System (NBES), for the implication of this research; teachers can revisit the existing curriculum for bridging with Vedic knowledge while teaching. So, it requires teachers' reorientation about Vedic pedagogy and the ways to blend this pedagogy with that of the training that the teachers’ obtain. This implies that there are many avenues of research to link Vedic wisdom with the current youth problems and the ways to mitigate them through orientation, discussion & reflection, short term Yoga sessions between teachers, parents and youths.